2017
DOI: 10.1177/0960327117715902
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum ammonia level and neurologic complications in patients with acute glufosinate ammonium poisoning: A prospective observational study

Abstract: Glufosinate ammonium poisoning can cause neurological complications even after a symptom-free period. We prospectively investigated the predictors of neurologic complications in acute glufosinate ammonium poisoning and the change of serum ammonia level as a predictor of patient's presence and recovery of neurologic complication. This prospective observational study collected data from consecutive patients diagnosed with acute glufosinate ammonium poisoning between September 2014 and June 2016. Serum ammonia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…On hatching day, 3 birds were randomly selected from each replicate for blood collection from the wing vein using a sterile syringe. Blood samples and frozen albumen samples were used for amino acid profile analysis using Hitachi 835-50 amino acid automatic analyzer and ammonia concentration analysis by Dimension Vista Ammonia method ( Cha et al, 2018 ). Samples were homogenized and then moved to a sealed tube with 10 mL of 6 mol/L HCl.…”
Section: Methodsmentioning
confidence: 99%
“…On hatching day, 3 birds were randomly selected from each replicate for blood collection from the wing vein using a sterile syringe. Blood samples and frozen albumen samples were used for amino acid profile analysis using Hitachi 835-50 amino acid automatic analyzer and ammonia concentration analysis by Dimension Vista Ammonia method ( Cha et al, 2018 ). Samples were homogenized and then moved to a sealed tube with 10 mL of 6 mol/L HCl.…”
Section: Methodsmentioning
confidence: 99%
“…El glufosinato de amonio (GLA) es un herbicida que se utiliza ampliamente en todo el mundo [31]. Un estudio realizado por Aris and Leblanc [32] encontró que un metabolito del GLA (ácido 3metilfosfinicopropiónico) podría detectarse en casi todas las muestras de suero sanguíneo de un grupo de pares madre-hijo, lo que indica una exposición universal y una potencial exposición transplacentaria.…”
Section: Glufosinato De Amoniounclassified
“…Un estudio realizado por Aris and Leblanc [32] encontró que un metabolito del GLA (ácido 3metilfosfinicopropiónico) podría detectarse en casi todas las muestras de suero sanguíneo de un grupo de pares madre-hijo, lo que indica una exposición universal y una potencial exposición transplacentaria. Aunque, la neurotoxicidad del GLA está bien documentada [31,33], los mecanismos subyacentes a través de los cuales GLA impactan el desarrollo del SNC siguen siendo desconocidos en gran parte. En este sentido, Dong, Guan [6] utilizaron un modelo animal de ratón para estudiar los efectos de la exposición prenatal del GLA.…”
Section: Glufosinato De Amoniounclassified
“…All patients with hyperammonemia upon ED arrival received a lactulose enema to lower their ammonia levels based on a serum ammonia level of 86 mg/dL, as high levels have been suggested to cause neurologic complications. 6,7 Some of the participants were excluded based on the following criteria: (1) age below 19 years, (2) poisoning involving other agents except alcohol, (3) transfer to another hospital after ED admission, and (4) insufficient data.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…A few studies reported that measuring serum ammonia levels at the ED or serial ammonia levels are useful for predicting neurologic complications, such as decreased mental status, seizure, or amnesia in glufosinate poisoning. [5][6][7] However, there is no study of whether serum ammonia concentration predicts inhospital mortality in the early phase of glufosinate poisoning. The sequential organ failure assessment (SOFA) and acute physiology and chronic health evaluation II (APACHE II) scoring systems are tools widely used for predicting the clinical outcomes of patients admitted to the intensive care unit (ICU).…”
Section: Introductionmentioning
confidence: 99%